Becoming a God hunter towards conversion in a Brooklyn tongue-speaking church. (March 2016) - Marina, Peter J
Based on over four years of ethnographic research in an Afro-Caribbean Pentecostal Church in Brooklyn, this article focuses on the process of becoming a religious seeker, or what I call a God hunter, towards conversion to a Pentecostal tongue-speaking church. Becoming a God hunter requires knowing the causes that explain religious seekership, the invariable sequence of interrelated events that are part of the process. It also requires gaining insight into motives at each stage in the process where potential converts arrive at their final decision to search for a religious group. This requires moving beyond a single set of essential variables, like crisis, or providing normative explanations to the motivation to become a religious seeker. Rather, this work explains the series of steps in a sequence of events that have a long and complex story in which individuals arrive at a point of convergence and decide to embark on a religious search. This article challenges the concept of crisis, used in both old and new scholarly models, to explain why someone decides to become a religious seeker. Final attention is given to the relevancy of continued academic debates on whether active or passive forces drive these individual decisions towards seekership.